Training and Timing Local Scalar Enrichments under Global Pragmatic Pressures. (29th May 2016) - Chemla, Emmanuel; Cummins, Chris; Singh, Raj
Abstract: Elementary sentences containing the quantificational determiner some seem to be ambiguous between a 'weak' existential meaning ∃ and a 'strengthened' some but not all meaning ∃ + . The strengthened meaning is commonly assumed to be the output of a general enrichment mechanism, call it G (for 'global'), that applies to the weak meaning of the sentence: G (∃) = ∃ + . The application of G has been shown to come with a processing cost (e.g. Bott & Noveck 2004 ). We used a self-paced reading task together with offline comprehension questions to investigate the interpretation of sentences containing some when embedded inside a disjunction, a position that G cannot access. Our findings suggest (i) that the strengthened meaning ∃ + is available in embedded positions, suggesting that a mechanism of local strengthening L must be available: L (∃) = ∃ +, (ii) that local enrichment can be facilitated by global pragmatic pressures (Chierchia et al . 2008 ; Mayr & Romoli 2014 ), (iii) that subjects can be quickly trained to systematically prefer one of G or L to the other, (iv) that application of L, like the application of G, comes with a processing cost. We highlight consequences of our findings for debates about the characterization of enrichment mechanisms, focusing on the relation between G and L .